Excellent energy storage performances for BaTiO3-based multilayer capacitors through synergistic high-entropy and superparaelectric-relaxor strategy - Dong Liu; Long Wang; Xinyi Wang; Ting Tang; Qi Wang; Jin-Rui Li; Bo-Ping Zhang; Li-Feng Zhu (Journal of Materiomics, 2025)
Dielectric capacitors with high energy storage performances are exceedingly desired for the next-generation advanced high/pulsed power devices that demand miniaturization and integration. However, poor energy-storage density (Urec) and low efficiency (η) resulted from the large remanent polarization (Pr) and low breakdown strength (BDS), have been the major challenge for the application of dielectric capacitors. Herein, a high-entropy strategy with superparaelectric relaxor ferroelectrics (SP-RFE) was adopted to achieve extremely low Pr and high BDS in BaTiO3 system, simultaneously. Due to the high BDS ∼800 kV/cm and low Pr ∼0.58 μC/cm2, high-entropy SP-RFE (La0.05Ba0.18Sr0.18K0.115Na0.115Ca0.18Bi0.18)TiO3 (LBSKNCBT) MLCCs exhibited high Urec ∼6.63 J/cm3 and excellent η ∼ 96%. What's more, LBSKNCBT MLCCs with high-entropy and SP-RFE characteristic also possess a good temperature and frequency stability. In a word, this work offers an excellent paradigm for achieving good energy-storage properties of BaTiO3-based dielectric capacitors to meet the demanding requirements of advanced energy storage applications.